Orthodontic treatment need in 11-13 years old shoolchildren in Republika Srpska - Umićević-Davidović Mirjana; Arapović-Savić Marijana; Arbutina Adriana (Serbian Medical Society - Dental Section, Belgrade, 2016)
Introduction Need for orthodontic treatment is determined by the severity of specific malocclusion. Orthodontic indices are used to objectively present treatment needs. The most commonly used is the Index of Orthodontic Treatment Need (IOTN). The aim of this study was to determine the need for orthodontic therapy in 11 to 13 years old schoolchildren in Republika Srpska. Material and Methods 1377 patients, 11 to 13 years old, were included in this study. The examinations were performed in elementary schools, using daylight, flat mirror and two-dimensional orthodontic caliper. Patients were ranked into 5 grades according to the Dental Health Component (DHC) and graded on a scale 1 to 10 for the Aesthetic Component (AC) of the IOTN index. Results According to the Dental Health Component (DHC), 79.23% of patients needed orthodontic treatment. Little and borderline orthodontic need was present in 27.74% and 24.83% children, respectively, while severe need was present in 19.98% and 6.68% respectively. 20.77% of subjects did not need orthodontic treatment. In regards to the Aesthetic Component (AC) (face appearance related to orthodontic need) little or no treatment was needed in 91.42% of subjects while 6.42% were borderline and 2.16% of subjects had severe relation between orthodontic need and facial appearance. Conclusion Due to the wide presence of orthodontic irregularities in schoolchildren 11-13 years old in Republika Srpska, it is important to introduce orthodontic indices in clinical practice in order to determine orthodontic treatment needs.